Interferences of urinary tract infection in the measurement of urinary nitrous oxide. Issue 9 (September 1996) - Apostoli, P; Gelmi, M; Alessio, L; Turano, A
Abstract : OBJECTIVES: To investigate the effective role of micro-organisms in producing N2O. METHODS: The N2O in either urine samples inoculated with 24 microbial strains or urine samples from patients with urinary tract infections were measured. RESULTS: Gram negative bacilli generally produced high amounts of nitrous oxide (N2O), whereas Gram positive cocci and yeasts did not. The production of N2O depends on the incubation time and follows exponential kinetics, reaching a plateau at 48 hours. Furthermore, the results of urinocultures agreed well with N2O concentrations found in urine samples: samples negative for bacteria were found to contain very low concentrations of N2O whereas those positive–for example, for Enterobacteriaceae–gave highest N2O values. CONCLUSION: The urinary tract infections caused by Gram negative bacilli are important confounding factors in biological monitoring practices of exposure to inhalation anaesthetics. The current methods adopted to avoid these factors (urine acidification, storage of samples at 4 degrees C) are not good enough because of the relative acid tolerance of some strains and the production of N2O directly into the bladder.